História e Memória Do Curso de Licenciatura em Química da Universidade Federal do Ceará (1995-2019): entre concepções e identidades curriculares - Silva, Wanderson Diogo Andrade da (2020)
This essay is based on the understanding that the Graduation in Chemistry Course in teachers formation of Federal University of Ceará (UFC), but the technical rationality and the Bachelor's Degree still persist. Considering this background, it is questioned: does the Graduation in Chemistry Course in teachers formation of Federal University of Ceará, in its path, present aspects that lead to the construction of professional teaching identity? To answer this and other questions, this essay's general objective is to understand the constitutive process of the Graduation in Chemistry Course in teachers formation of UFC (1995 – 2019) in the context of the teaching de-professionalization. As specific objectives, this essay aimed: (i) to analize the official documents of identity that led to its curricular re-organization; (ii) to identify the influence of the teachers trainers of the graduation in Chemistry during the curricular settin-up and re-organization process of the course; and (iii) to characterize reorganization process of identity of the Chemistry teachers from curricular transformations and the expressed insights in the investigated speeches. The embraced methodological construction is based on the qualitative approach, with emphasis on thematic oral history and the documentary research. Three professors (two of them are retired and only one is activate) participated in the oral data generation, which were analized through Discursive Textual Analysis. The analyses highlight that the course was created not to supply the lack of Chemistry teachers in the state but for bachelor's degree to not be disrupted, and the presence of the technical rationality along its existence is very significant. The changes that have happened barely attended the guidelines for teacher training, particularly in terms of trainers' acting, hegemonically, bachelor's degree. In a nutshell, the disciplines of Teaching Practice are considered redeeming in the undergraduate students pedagogical training, removing the teacher's responsability from other curriculum components of their obligations in terms of teacher training. For the redefinition of UFC's Chemistry teachers training, it is pointed out the importance of the continuous training of the trainers, particularly regarding to teaching and to education, among other proposals.